TEKNIK TEXT MINING UNTUK MENGANALISIS WACANA MODERASI AGAMA: WAWASAN DARI RUANG DIGITAL INDONESIA - Tabroni, Roni; Reza Shaker, Ardekani; Yunani, Ahmad (Jurnal Lektur Keagamaan, 2024)
The socialization of religious moderation discourse in the digital space requires an effective strategy to engage the Indonesian populace. This study aims to understand the patterns and forms of religious moderation discourse in the Indonesian digital space from 2020 to 2023 and to assess the effectiveness of text mining techniques in this context. A mixed-method approach, combining digital humanities with quantitative text mining and qualitative discourse analysis, was employed to analyze the discourse on religious moderation. The findings indicate that the discourse is dominated by the term "Indonesia," highlighting the intertwining of religious moderation with nationalism. The prominence of "Indonesia" as a keyword suggests that the promotion of religious moderation values aligns closely with nationalistic sentiments. Additionally, the discourse is significantly influenced by political activities, with politicians' pragmatic values serving as a means to reach various segments of society, albeit not as a long-term strategy. To enhance the socialization of religious moderation, it is crucial to evaluate and refine current strategies. Analyzing the patterns and forms of this discourse can provide insights for more effective dissemination in the digital space. This evaluation will help in better promoting the values of religious moderation, ensuring they resonate with broader societal values and reach a wider audience.